The Effect of Environmental Variation on Feed Consumption and Some Physiological Parameters of Arabi Sheep and Local goats: Blood pictures and concentration of some hormones - Ola M. Karam; Waleed Y. Kassim (Zien Journals, 2022)
This study was conducted in the animal field of the College of Agriculture - University of Basra between 1/10 to 12/29/2021, to investigate the influence of environmental variance on some blood pictures and the concentrations of some hormones in Arabi sheep and local goats, Six male of Arabi lambs breed and 6 male of the local black Iraqi goat breed at the age of (7-8) months and with an average weight of (20.85, 20.30) kg were divided into two groups (each type in one group).The daily temperatures and humidity were recorded throughout the study period (to extract the average temperature and humidity during the months of the experiment). The results indicated that there was no significant effect of animal type on blood pictures (white blood cells, red blood cells, hemoglobin concentration, packed cell volume), while the concentrations of vitamin C, thyroxine and cortisol increased in sheep compared with goats. Values of red blood cell count, hemoglobin concentration, packed cell volume, vitamin C and cortisol significantly (P <0.05) decreased as temperature decreased. However, the concentration of thyroxine increased during low temperature>
Keywords: Environmental variation; Sheep; Goats; Temperature